JNK-dependent downregulation of FoxO1 is required to promote the survival of fibroblast-like synoviocytes in rheumatoid arthritis. Issue 9 (8th May 2014) - Grabiec, Aleksander M; Angiolilli, Chiara; Hartkamp, Linda M; van Baarsen, Lisa G M; Tak, Paul P; Reedquist, Kris A
Abstract : Background: Forkhead box O (FoxO) transcription factors integrate environmental signals to modulate cell proliferation and survival, and alterations in FoxO function have been reported in rheumatoid arthritis (RA). Objectives: To examine the relationship between inflammation and FoxO expression in RA, and to analyse the mechanisms and biological consequences of FoxO regulation in RA fibroblast-like synoviocytes (FLS). Methods: RNA was isolated from RA patient and healthy donor (HD) peripheral blood and RA synovial tissue. Expression of FoxO1, FoxO3a and FoxO4 was measured by quantitative PCR. FoxO1 DNA binding, expression and mRNA stability in RA FLS were measured by ELISA-based assays, immunoblotting and quantitative PCR. FLS were transduced with adenovirus encoding constitutively active FoxO1 (FoxO1ADA) or transfected with small interfering RNA targeting FoxO1 to examine the effects on cell viability and gene expression. Results: FoxO1 mRNA levels were reduced in RA patient peripheral blood compared with HD blood, and RA synovial tissue FoxO1 expression correlated negatively with disease activity. RA FLS stimulation with interleukin 1β or tumour necrosis factor caused rapid downregulation of FoxO1. This effect was independent of protein kinase B (PKB), but dependent on c-Jun N-terminal kinase (JNK)-mediated acceleration of FoxO1 mRNA degradation. FoxO1ADA overexpression in RA FLS induced apoptosis associated with altered expression of genes regulating cell cycle and survival, including BIM, p27 Kip1 and Bcl-XL. Conclusions: Our findings identify JNK-dependent modulation of mRNA stability as an important PKB-independent mechanism underlying FoxO1 regulation by cytokines, and suggest that reduced FoxO1 expression is required to promote FLS survival in RA.